Calculation, Deposit, and Reporting of Value Added Tax (VAT) Based on E-Invoice at CV Karunia Sejati - Madao, Henny Pandin; Walandouw, Stanley Kho; Tangkuman, Steven Josia (PT FORMOSA CENDEKIA GLOBAL, 2024)
Tax is the largest source of income for the state which is used to advance the country's economy. Every country must have income from taxes. In the 2024 Indonesian State Budget, the target for tax revenue in Indonesia is IDR 2,307.8 trillion from state revenue or IDR 2,781.3 trillion, which is around 80% of state revenue. This study aims to calculate, deposit, and report VAT based on E-Invoice at CV Karunia Sejati. This study uses qualitative research with a descriptive method with a qualitative approach. The study shows that the results of the calculation of Value Added Tax (VAT) belonging to CV Karunia Sejati based on Law No. 7 of 2021 only occur when issuing output tax invoices, while the Company does not receive input tax invoices; The deposit and reporting process in 2023 was delayed which resulted in the Company paying administrative sanctions in accordance with the provisions of the law